A Canadian University Counsellors: A Survey of Theoretical Orientations and other Related Descriptors - Warner, Ronald E. (Canadian Journal of Counselling and Psychotherapy, 2011)
This study gathered data on Canadian university counsellors' preferred theoretical orientation and their ranking of the three most influential counsellors/psychotherapists. Data was also collected on primary emphasis in graduate school, years of counseling experience, highest degree, gender and age. Results indicated that the sample was predominantly eclectic in theoretical orientation, with person-centred and cognitive behavioural orientations in second and third places respectively. The ranking of the most influential counsellors/psychotherapists were Carl Rogers, Aaron Beck and Albert Ellis. Comparisons were made with the preferences of both Canadian and American psychologists.